Sustainability assessment of feedstock powder reuse for directed laser deposition - Joju, J. (2024)
In this paper, the results of a sustainability assessment for the study of the reuse of un-melted feedstock powder in Directed Laser Deposition are reported. Ti6Al4V ELI powder was employed as material for the study and the un-melted powder was collected and reused as raw material for subsequent cycles of deposition. A total of three deposition cycles were completed and data for a Life Cycle Assessment were compiled. From the experimental work results, the un-melted powder suffered minimal changes that did not affect the critical characteristics analysed. The Life Cycle Assessment showed that reusing the powder, and consequently reducing the total mass of raw material consumed, resulted in significant environmental benefits. All the categories considered saw approximately a 15%–25% environmental impact reduction when reusing the powder as compared to a scenario when only virgin material is used. Most of the environmental footprint was seen in the production of the powder as compared to the transportation and manufacturing stages. The production phase, when reusing and when using only virgin powder, accounted for 89% and 95% of the total environmental impact respectively. This meant the environmental benefits due to the lower mass of powder used far outweighed the increase in water and energy required for the powder reuse process in the manufacturing stage. Thus, feedstock powder reuse in Directed Laser Deposition process is seen to have a significant environmental benefit as compared to the usage of virgin powder alone.